Educational Intervention on Knowledge of Autism Spectrum Disorder among Accredited Social Health Activists in a Rural Field Practice Area of a Postgraduate Public Health Institute in West Bengal, India - Kirtesh Tiwari; Jayita Pal; Sanjoy Kumar Sadhukhan; Lamabam Harit Singh (International Journal of Human and Health Sciences (IJHHS), 2026)
Autism Spectrum Disorder (ASD) is an increasingly recognized neurodevelopmental disorder affecting a significant number of children worldwide. In India, limited awareness and inadequate developmental screening contribute to delayed identification, particularly in rural settings. Accredited Social Health Activists (ASHAs), as frontline health workers, can play an important role in early identification of developmental disorders if adequately trained. The present study aimed to assess baseline knowledge regarding autism among ASHA workers in West Bengal, India, and to evaluate the effect of a structured educational intervention on their knowledge. An institution-based quasi-experimental study was conducted in the Rural Health Unit and Training Centre, Singur, West Bengal, India, using a before-and-after design without a control group, between March 2025 and March 2026. The study included 58 ASHA workers selected by simple random sampling. Baseline knowledge was assessed using the validated Knowledge about Childhood Autism among Health Workers (KCAHW) questionnaire. A structured educational intervention was delivered using PowerPoint presentations, posters, flipcharts, and leaflets in the local language. Knowledge was reassessed immediately after the intervention and at three-month follow-up. The mean baseline knowledge score was 0.79±1.94 with a median of 0. Knowledge improved significantly immediately after the intervention, with a mean score of 8.17±2.69 and median of 8. At three-month follow-up, the mean score was 5.83±2.86 with a median of 5. Friedman test showed a statistically significant difference across the three time points (p